Compound heterozygous mutations in MICU1 cause myopathy with extrapyramidal signs in two Chinese pedigrees - Li, Jieling; Liu, Hu; Gan, Xiaoming; Ou, Yuexu; Duan, Yuanhui; Cao, Jie (Frontiers in Neurology, 2025)
BackgroundAlthough MICU1-related myopathy with extrapyramidal signs (MPXPS) has been reported globally, its genotypic and phenotypic spectrum in Chinese populations remains poorly characterized. Here we investigate two unrelated Chinese pedigrees with MPXPS caused by novel compound heterozygous MICU1 mutations, addressing this critical knowledge gap.MethodsWe retrospectively analyzed the clinical features of four children from two unrelated families with MPXPS caused by compound heterozygous mutations in the MICU1 gene. Whole exome sequencing (WES) was performed on the probands and their parents. Sanger sequencing was used to validate the candidate gene variants. A literature review and summary of cases with bi-allelic mutations in MICU1 leading to MPXPS were conducted.ResultsFour children from two unrelated families presented with elevated muscle enzymes and liver function abnormalities. In Family 1, the proband (older brother, 8 years) exhibited typical MPXPS symptoms including motor dysfunction and cognitive impairment, while his younger brother (4 years) remained asymptomatic though with elevated muscle enzymes. WES identified compound heterozygous variants c.156G > A and c.235G > T in the two siblings. In Family 2, the proband (older sister, 3 years 4 months) manifested early signs including pes planus and attention deficits, whereas her younger sister (1 year 6 months) showed no clinical manifestations despite biochemical abnormalities. WES identified compound heterozygous variants EXON4-8 heterozygous deletion and c.1,372C > T.ConclusionThe phenotypic variations between the sibling pairs across both pedigrees may indicate age-dependent disease progression. The four children in this study with MPXPS due to compound heterozygous mutations in the MICU1 gene showed phenotypic differences compared to previously reported MPXPS cases, indicating a positive correlation between MICU1 loss of function and the severity of the phenotype, demonstrating a clear genotype–phenotype correlation.